2013
DOI: 10.21859/isv.7.4.29
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization and Standardization of New Infectious Bursal Disease Virus for Development of a Live Vaccine

Abstract: Background and Aims: Infectious bursal disease (IBD) is an acute contagious viral disease of birds worldwide. The causative virus induces a persistent immune suppression following destroy B lymphocytes precursors in bursal lymphoid follicles. Vaccination is the main strategy for prevention of the disease in commercial poultry industry. Materials and Methods:To produce a live vaccine against the disease, an new virus strain was isolated from the affected bursa of Fabricius. Diagnostic serological tests, histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…After preparing the vaccine, the clinical evaluation was performed on 60 SPF chickens in two groups via ocular and drinking water routes. The results showed the vaccine efficacy and the induction of sufficient immunity (29).…”
Section: Vaccine Related Studiesmentioning
confidence: 93%
See 2 more Smart Citations
“…After preparing the vaccine, the clinical evaluation was performed on 60 SPF chickens in two groups via ocular and drinking water routes. The results showed the vaccine efficacy and the induction of sufficient immunity (29).…”
Section: Vaccine Related Studiesmentioning
confidence: 93%
“…Developing of new vaccines using newly discovered strains is one of the procedures to develop new vaccines. In 2013, Ebrahimi et al isolated and identified a new IBDV strain named IBD07IR for vaccine development (29). The IBD07IR strain was identified as one of the vvIBDV strains using different serological tests and restriction fragment length polymorphism (RFLP) (29).…”
Section: Vaccine Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The IBDV antigen was prepared by injection of IBD07IR intermediate strain [14] into chorio-allantoic membrane of 9-11-day-old SPF chicken embryos (obtained from Razi Institute, Karaj, Iran). After 5 days incubation at 37°C, the amnioallantoic fluid and infective embryo were harvested, grinded, and clarified by centrifugation at 5000 rpm for 30 min at 4°C.…”
Section: Inactivated Ibdv Antigen Preparation and Validationmentioning
confidence: 99%